2018
DOI: 10.3892/ol.2018.8363
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of serine/threonine protein phosphatase 5 enhances gemcitabine sensitivity by promoting apoptosis in pancreatic cancer cells in�vitro

Abstract: Abstract. The targeting protein of serine/threonine protein phosphatase 5 (PPP5C) has been reported to be present in various malignancies. However, its functional role in pancreatic cancer (PC) remains unknown. In the present study, the function of PPP5C in PC cells treated with the first-line drug gemcitabine (GEM) was investigated. Short hairpin (sh)RNA targeting PPP5C was constructed to knockdown PPP5C in PANC-1 cells. Cell cycle and apoptosis analyses were performed in order to investigate the mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It is unquestionable that p53 also plays a crucial role in the drug resistance of various cancers . Thus, we investigated whether SRPK2 regulated drug resistance in a p53‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…It is unquestionable that p53 also plays a crucial role in the drug resistance of various cancers . Thus, we investigated whether SRPK2 regulated drug resistance in a p53‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…PPP5C plays a pivotal role in regulating cell growth, and studies have shown thatPPP5C knockdown could inhibit cancer cell proliferation [ 40–42 ]. Zhu et al found that knockdown of PPP5C could enhance gemcitabine sensitivity by promoting apoptosis of pancreatic cancer cells; and more cells in G0/G1 phase arrest were observed in this condition [ 43 ]. In this work, we found that the mRNA expression of PPP5C was higher in pancreatic adenocarcinoma than in normal tissues and that its level correlated with tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PPP5C mentioned in this study is a cancer-promoting factor in many cancers ( 20 , 21 ). It has been less studied in pancreatic cancer and is only known to make tumors resistant to gemcitabine ( 16 ). In this section, we would analyze our results through the lens of relevant literature in order to find the immune-related genes of colon cancer, establish a prognostic risk score model, and verify its accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…On the cancer side, the role of PPP5C in proliferation and cell survival and its unique structure make it a potentially attractive therapeutic target, and elevated PPP5C expression has been found to increase proliferation in most cells in breast and renal cancer clinical studies ( 15 ). The role of PPP5C in pancreatic cancer is similar to that in other cancers: it leads to the progression of pancreatic cancer by enabling tumors to develop resistance to gemcitabine ( 16 ). Therefore, targeting the inhibition of PPP5C is particularly important in the treatment of pancreatic cancer, while miRNAs regulate the properties of mRNA expression by binding to its 3’-UTR ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%